Sistemas de Custeio em Instituições Hospitalares: Estudo Comparativo entre os Hospitais da Cidade de Muriaé - MG - Silva, Edson Arlindo; Abreu, Carlos Alberto (Contabilidade Vista & Revista, 2009)
In this research we aimed to present the results of an empirical-theoretical research about the funding systems used by hospital organizations in Muriaé city -MG, considered an important pole in Zona da Mata Mineira east region and, and in the country, and in the country, referring to the cancer treatment through the Centro Brasileiro de Oncologia, called Fundação Cristiano Varellla. While developing this research we investigated the most common funding systems applied by the hospital organizations in Muriaé, as all the experiences of those with the ABC (Activity Based Costing) method. Since the funding management in any kind of organization we represent a fundamental management tool essential for the resources control. We used the structured questionnaire in this study in five hospitals in Muriaé, corresponding to 100% of the studied population. The study started in 2005 e finished in the first semester of 2006. The answers were tabulated using the Excel program. The research reveled that the majority of hospitals in Muriaé operate using the absorptive funding system instead of the ABC method, that is still used a little. One argument for such result may be the lack of knowledge about the ABC method and the lack of managers specific hospital knowledge.